Climate change anxiety in the scientific community: an exploratory study with Chilean climate change-related scholars - Sapiains, Rodolfo; Azócar, Gabriela; Palomo-Vélez, Gonzalo; Rondanelli, Roberto (Frontiers in Psychology, 2025)
BackgroundEco-anxiety or climate change anxiety can be defined as a chronic fear of environmental doom that for some people might trigger clinical psychological issues. Although the study of this phenomenon is growing, there is not much understanding of the psychological consequences that studying climate change can have on scholars who are overexposed to information that is generally full of negative projections. This study aims at exploring to what extent continued exposure to scientific information about climate change affects those who research it.MethodsWe conducted an online survey with a sample of climate scientists from Chile (n = 249), one of the most vulnerable countries to climate change. A Spanish-translated and adapted version of Clayton and Karazsia’s climate change anxiety scale was used along with single items to assess self-reported climate change anxiety, and sociodemographic factors.ResultsMost Chilean climate change scientists are being emotionally affected by climate change. However, high levels of self-reported ecoanxiety contrast with more moderate results when measuring ecoanxiety as a whole and in both subscales, cognitive-emotional and functional. Women, young people, and those who do not have children, express more emotional and functional impacts. Social scientists showed higher climate change anxiety levels than natural scientists.ConclusionAlthough for most participants climate change anxiety is not affecting life functioning, this does not necessarily mean that it will not affect them in the future. We believe that research centres and teams must develop strategies to help scholars cope with the psychological consequences of working on climate change.